Creche: desafios e possibilidades uma proposta curricular para além do Educar e Cuidar - André, Rita de Cássia Marinho de Oliveira (2016)
This research aims to determine and understand how the pedagogical intention in the practice of daycare educators and inventive and intelligent capacity of the knowledge of babies, stitched together by affection, break with the welfare and "schooling" actions. Based on these premises, curriculum is built from listening the multiple forms of language used by babies and small children, in observation of what they already know in motor and cognitive development indicators, and Psychic Risk indicators for child development (IRDls). Under this scope, spaces become welcoming environments and routine guided at moments ensure the comprehensive development of babies and young children attending day care. The research begins with a historical review about the brazilian kindergarten. It follows with the theorization of the curriculum as a support to questions about educational practices and, more specifically, about the actions triggered in early childhood education based on the curriculum guidelines of the Ministry of Education. The chosen methodological approach contemplates the qualitative research. It is used the literature search and document analysis on curriculum conceptions of the early childhood and about a nursery maintained by a health institution, located on the south side of São Paulo. As a result, it was concluded that there are two paths in the construction of the nursery teacher job. The first strives for anonymity, the generalization and therefore the emptying of subjectivity. It is taken by those who credit to knowledge and technical absolute truths that can be taught and consequently learned. The second, which supports this research, is permeated by symbolic marks that allow babies and toddlers advirem as beings multiply languages, supported by a curriculum that addresses this listening and taking into account its limits and its possibilities